The Road Less Travelled in Access to Higher Education - Peter Ogudoro (University of Aberdeen, School of Education, 2016)
This feature identifies the licencing examinations professional bodies conduct as a road less travelled in access to higher education. Such examinations enable successful candidates to gain Professional Diplomas which are equivalents of university Bachelor's degrees and can grant the holders access to postgraduate academic programmes. The feature which is based on a doctoral research study conducted in Nigeria argues that the elastic capacity of professional bodies for access to higher education may be a cost effective platform for dealing with the higher education access challenge in the case country and many other societies with similar challenges.